Small states face big challenges - Venner, Dwight (2009)
Defines and identifies small states. Sets out the economic features that are associated with such states and that influence the impact of the crisis. Presents as an example, the case of the Eastern Caribbean Currency Union (ECCU) and its response to the crisis. Presents a view on the role of the international community in assisting small states to prepare for and to mitigate the impact of such crises.